Membangun Kebiasaan Baik Literasi melalui Pemanfaatan Buku Cerita Digital di SD Harapan Kasih - Feby Riski Ariyani; Hasna Dhea Santika; Nurwulan Nurwulan (Program Studi PGSD Kampus UPI di Serang, 2021)
Utilization of literacy reading resources is one of the efforts that can be made by teachers to improve students' literacy skills. However, in the school where this research was conducted, the authors did not find any reading literacy activities carried out during distance learning. Teachers only rely on textbooks. Therefore, the author tries to implement the activity of reading digital story books which is one of the efforts to foster a student's passion for reading, of course, being part of efforts to improve literacy skills. The digital storybooks used are sourced from the website Badan Pengembangan dan Pembinaan Bahasa Kementerian Pendidikan Indonesia. This digital storybook is packaged in an interesting, diverse, and contains cultural and character values. In this study, the author wanted to know the students' responses to the digital storybook. The result turned out that students were happy with the digital storybooks that were presented, even the activity of reading these digital storybooks became a new habit that students always asked for. In conclusion, the use of digital storybooks sourced from the website Badan Pengembangan dan Pembinaan Bahasa Kementerian Pendidikan Indonesia has the potential to support literacy activities carried out before starting distance learning at Harapan Kasih Elementary School because it can attract students' attention.